Pass-through of external shocks along the pricing chain: A panel estimation approach for the euro area - Bettina Landau; Frauke Skudelny (European Central Bank (ECB), 2009)
In this paper we analyse in a mark-up framework the pass-through of commodity price and exchange rate shocks to the main components of producer and consumer prices. Thereby we link movements in prices at the different production stages as firms set their prices as a mark-up over production costs. The empirical results reveal significant linkages between different price stages in the euro area. The overall results are roughly in line with the literature and provide insight into the effects at different stages of the production chain. Non-energy commodity prices turn out to be important determinants of euro area prices.
Keywords: E31; E37; 330; commodity prices; consumer prices; exchange rate; Pass-Through; producer prices; Rohstoffpreis; Exchange Rate Pass-Through; Inflationskonvergenz; Verbraucherpreisindex; Eurozone; EU-Staaten